GENOCIDE DAN WAR CRIME: SEBUAH PERBANDINGAN DARI SUDUT PANDANG GRAVE BREACHES (PELANGGARAN HAK ASASI MANUSIA BERAT) - Indah Sari (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
This writing propose to explain some criterions of grave breaches, which is constituted of genocide, war crime, aggression and crime against humanity. Genocide means any of the following acts committed with intent to destroy, in whole or in part, a national, ethnical, racial or group. War Crimes: Namely, violations of the laws or customs of war. Such violations shall include, but not be limited to, murder, illtreatment or deportation to slave labour or for any other purpose of civilian populations of or in occupied territority, murder or ill-treatment of prisoners of war or persons on the seas, killing of hostages, plunder of public of private property, wanton destruction of cities, town or villages, or devastation not justified by military necessity. Finally, this writing focused about some differences between Genocide and War Crime Keywords: Human Rights, Grave Breaches, Genocide, War Crime.